Role of phosphoric acid and activated carbon in degumming and bleaching stages of Tra catfish oil refining process - Pham, Thi Hoan; Ngo Thanh Binh (Journal of Technical Education Science, 2020)
The purpose of the present study was to investigate the efficiency of phospholipid removal using phosphoric acid and tra catfish (Pangasianodon hypophthalmus) oil bleaching using activated carbon. Crude oil was extracted from tra catfish fat, a by-product, by hot water. Crude oil had phosphorus content of 19.63 mg/kg, Abs228nm of 0.91, melting and solidification points of 33.8oC and 24oC, respectively. After the refining process, chemical and physical properties of fish oil had many advantaged changes. Phosphorus content was reduced to 4.48 mg/kg, Abs228nm, melting and solidification points were decreased to 0.32, 10.2°C and -2.0°C, respectively. Besides, quality parameters such as peroxide value (4.22 meq O2/kg), iodine value (67.88 gI/100g), and saponification value (162 mg KOH/g) were analyzed. Moreover, total content of unsaturated fatty acids was 60.6% including palmitoleic, oleic, linoleic, γ-linolenic, paullinic, eicosadienoic, dihomo-γ-linolenic, erucic acids. Refined tra catfish oil is a pale yellow, liquid state at ambient temperature without strange odor.